Unsteady flow and heat transfer optimization of viscous fluid with bioconvection over a rotating stretchable disk and gyrotactic motile microorganisms - Mazhar Hussain; Samya Shahid; Noreen Sher Akbar; Mohammed Kbiri Alaoui (Case Studies in Thermal Engineering)
The ultimate aim of the present paper is to investigate thermal, mass and microorganism transfer rates in convective flow. Nanofluid's heat transfer along with unsteady laminar flow on stretched rotating disk with motile microorganism bioconvection is numerically analyzed. The novelty of study is to construct a framework that combines microorganisms along with energy equation to analyze how can they be helpful in making a system more efficient like heat transfer enhancement in cooling devices and heat transfer exchanger etc. The model combined energy and concentration equation of microorganisms along with modified momentum equations, considering impact of internal heat generation and nanoparticles diffusion. Impact of unsteady variable (S), disk stretching variable (α), Prandtl number (Pr), Lewis number (Le) are analyzed graphically to understand the thermal and flow behavior. The boundary value problem is numerically solved using shooting method with Runga-Kutta technique by converting equations into initial value problem. Graphical results indicates that parameters like increment of unsteady effects helps in dissipation of thermal energy rapidly and bioconvection evidently influenced velocity, temperature and microorganism profile by thinning the microorganism layer, showing valuable results for optimizing thermal systems like in aerospace engineering where spacecraft undergo extreme temperature due to friction between spacecraft and atmosphere.